The Extent of The Availability of Dimensions of Workplace Spirituality in The Mosul Municipality Directorate: An Analytical Study (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The current research aims to identify the availability of spirituality dimensions in the workplace, represented by (meaningful work, a sense of community, the fit between the values of the individual and the organization, and job engagement)  among workers in the Mosul Municipality Directorate ,the research relied on the questionnaire to collect data while the statistical program (SPSS V26) and the descriptive analytical method were used to analyze the data and its community is represented by all the workers in the directorate, whose number is (336) while its sample was intentional as it was limited to workers with certificates (high school to doctorate) and their number was (221).The research reached a set of conclusions, including the existence of a clear difference regarding the realization of the dimensions of workplace spirituality and its importance at the level of the researched organization, as well as a set of proposals, including giving increased attention to workplace spirituality by managers. .